ANALISIS HUKUM PERSEKONGKOLAN DALAM TENDER PADA PUTUSAN KPPU NOMOR 13/KPPU-/2015 - Muhamad Rifqi Fajrin (2020)
This research was conducted for the requirements of obtaining a master's degree in law with the title Legal Analysis of Conspiracy in Tender in KPPU Decision Number 13 / KPPU-L / 2015. The problem discussed in this study is regarding the legal analysis that occurs as a result of the tender conspiracy committed by the Actors in KPPU Decision Number 13 / KPPU-L / 2015. The research method used is normatif approach with type of case approach and legislation approach. Normatif research is carried out by researching library materia or seecondary data as basic material to be researched using qualitative analysis by preskriptif data processing. From the results of this study, it can be concluded that the legal analysis that occurs from the existence of tender conspiracy is able to create obstacles for other bidders who actually have more potential to win and can cause harm to the State